Enigmatic declines of Australia's sea snakes from a biodiversity hotspot - Lukoschek, V.; Beger, M.; Ceccarelli, D.; Richards, Zoe; Pratchett, M. (Elsevier, 2013)
Declines in the abundance of marine vertebrates are of considerable concern, especially when they occur in isolated locations relatively protected from most major anthropogenic disturbances. This paper reports on sustained declines in the abundance and diversity of sea snakes at Ashmore Reef, a renowned biodiversity hotspot in Australia's Timor Sea. Surveys conducted in eight years between 1973 and 2010 recorded the highest abundances (average 42-46 snakes day-1) and species richness (nine species) in 1973 and 1994. In 2002 abundance had declined by more than 50% (21 snakes day-1) and only five species were recorded. Since 2005 abundances have been consistently low (1-7 snakes day-1), with just two species, Aipysurus laevis andEmydocephalus annulatus, recorded in significant numbers. Despite extensive searches since 2005 (especially in 2010) five species of sea snake historically abundant at Ashmore Reef have not been sighted and are presumed to have become locally extinct. These species include three Timor Sea endemics Aipysurus apraefrontalis, Aipysurus foliosquama, Aipysurus fuscus, and one Australasian endemic Aipysurus duboisii. Declines in the abundance and diversity of sea snakes at Ashmore Reef cannot be attributed to differences in survey methods among years. Ashmore Reef was declared a National Nature Reserve (IUCN Category 1a) in 1983 and, although the causes for the declines are not known, this protection has not prevented their occurrence. We discuss possible causes for these enigmatic declines however, in order to implement effective management strategies, studies are needed to determine why sea snakes have disappeared from Ashmore Reef. © 2013 Elsevier Ltd.